2022
DOI: 10.5851/kosfa.2021.e75
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Aroma Profile of Highly-Marbled Beef according to Quality Grade using Electronic Nose Sensors Data and Chemometrics Approach

Abstract: Ethics approval (IRB/IACUC) (This field may be published.) This article does not require IRB/IACUC approval because there are no human and animal participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…The PCA analysis was also used to distinguish dog foods according to the similarity of the nutritional profile of the group [ 9 ]. Recent studies have shown that multivariate analysis of E-nose data can distinguish the aroma of beef and pork [ 41 ] and classify the aroma profile of beef according to quality grade [ 42 ]. In this study, dog foods were separated according to the sensory characteristics of taste (bitterness, saltiness, and sourness) and VACs through the multivariate analysis of chemical sensory analysis data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCA analysis was also used to distinguish dog foods according to the similarity of the nutritional profile of the group [ 9 ]. Recent studies have shown that multivariate analysis of E-nose data can distinguish the aroma of beef and pork [ 41 ] and classify the aroma profile of beef according to quality grade [ 42 ]. In this study, dog foods were separated according to the sensory characteristics of taste (bitterness, saltiness, and sourness) and VACs through the multivariate analysis of chemical sensory analysis data.…”
Section: Resultsmentioning
confidence: 99%
“…These results will provide fundamental information on developing new dog foods with improved palatability and on understanding the sensory characteristics of different varieties of dog food. distinguish the aroma of beef and pork [41] and classify the aroma profile of beef according to quality grade [42]. In this study, dog foods were separated according to the sensory characteristics of taste (bitterness, saltiness, and sourness) and VACs through the multivariate analysis of chemical sensory analysis data.…”
Section: Analyses Of Taste Components and Volatile Compounds Patterns...mentioning
confidence: 99%
“…This phenomenon is related to the reducing sugars, the release of free amino acids and peptides, and the increase in the content of inosine monophosphate (IMP), guanosine monophosphate (GMP), inosine, and hypoxanthine due to the breakdown of ribonucleotides [ 94 96 ]. In addition, flavor enhancement in aged beef is associated with the production of other flavor-related volatile compounds such as n-aldehydes (e.g., pentanal and hexanal) and ketones, which also contain lipid oxidation-related products [ 10 , 12 , 97 ]. These flavor precursors interact with each other throughout the cooking process, generating new flavor components [ 12 ].…”
Section: Changes In Taste Characteristics Of Meat Due To Agingmentioning
confidence: 99%
“…contain lipid oxidation-related products [10, 12,97]. These flavor precursors interact with each other throughout the cooking process, generating new flavor components [12].…”
Section: A C C E P T E Dmentioning
confidence: 99%